Perancangan Puzzle Sudoku Warisan Hanacaraka Menggunakan Metode Design Thinking dan Game Design - Novida Nur Miftakhul Arif (ULTIMART Jurnal Komunikasi Visual, 2022)
Learning Javanese script or Hanacaraka unfortunately do not have any pragmatic benefits for majority of people. It is not surprising if the passion to learn Javanese script is low especially with children of elementary school and middle school who receive the learning material in schools. Even though with preserving Javanese script, we will obtain many benefits such as building powerful national character. Preservation actions needs to be taken, one of them is utilizes persuasive method with suitable media for children. Warisan Hanacaraka, an Android mobile game with gameplay of Sudoku puzzle, will becomes the suitable media to answers the challenge. A qualitative approach is used to describe the idea of Warisan Hanacaraka development in this paper. This video game was developed with design thinking and game design which is adapted to Sudoku gameplay. Warisan Hanacaraka can be a new variation of Sudoku puzzle, especially by injecting distinctive traditional. Relevant elements of traditional cultures such as batik, folklore and tamples, uniquely tailored with user interface, user experience, gameplay and story to makes this educational game stand out from the crowd. Warisan Hanacaraka is not only becomes a potential method to growing interest of learning Javanese script, but it can be a positive usage of smartphone because it will stimulate development of cognitive and affective skills. Keywords: hanacaraka; application; game; sudoku